Anxiety and Depression Profile Is Associated With Eating Disorders in Patients With Irritable Bowel Syndrome - Melchior, Chloé; Desprez, Charlotte; Riachi, Ghassan; Leroi, Anne-Marie; Déchelotte, Pierre; Achamrah, Najate; Ducrotté, Philippe; Tavolacci, Marie-Pierre; Gourcerol, Guillaume (Frontiers in Psychiatry, 2020)
Objective: To compare the prevalence of anxiety and depression states and eating disorders between patients with irritable bowel syndrome (IBS) and healthy volunteers without IBS. Methods: IBS patients according to Rome III criteria referred to our tertiary care center for therapeutic management and matched volunteers without IBS were prospectively included. Eating disorders (ED) were screened by SCOFF-F questionnaire. IBS symptom severity (IBS Symptom Severity Score), stool consistency (Bristol Stool Scale), anxiety and depression levels (Hospital Anxiety and Depression Scale), and quality of life (validated GastroIntestinal Quality of Life Index) were assessed by validated self-questionnaires. Results: 228 IBS patients and 228 healthy volunteers were included. Mean age was 42.5 ± 13.9 years with mainly women (76.7%). Among IBS patients, 25.4% had positive SCOFF-F compared to 21.1% of volunteers. IBS patients more frequently had a lower body mass index (BMI) than volunteers (p<0.0001). IBS patients with ED had poorer quality of life and more stressful life events (p= 0.02) than IBS patients without ED. The prevalence of anxiety and depression was significantly higher in IBS patients with ED than in volunteers without ED, respectively (19.0% vs 1.9%, p=0.00) and (60.3% vs 19.7%, p<0.0001). Conclusions: The prevalence of ED assessed with positive SCOFF-F questionnaire was not significantly different between IBS patients and healthy volunteers. The combination of IBS and ED was associated with higher levels of anxiety or depression and poorer quality of life.